Half-Told Tales : Dilemmas of Meaning in Three French Novels - Stewart, Philip, 1940- (North Carolina studies in the Romance languages and literatures, 2019)
Philip Stewart demonstrates that in each of three novels--Marivaux's La Vie de Marianne, Diderot's La Religieuse, and Rousseau's Julie ou la Nouvelle Heloise--the characters' sincerity disguises how incompletely the meaning of their own experience is resolved. However clear their premises, ambiguity creeps in, compromising or subtly contradicting the clarity of their vision. Stewart reveals these countercurrents or repressive rhetorical strategies and situates them with respect to the broad thematics of each work.